Understanding the Regulation of the Use of Artificial Intelligence Under International Law - Gaho, Festina (Verdict: Journal of Law Science, 2024)
The development of artificial intelligence (AI) has revolutionized various aspects of human life, from the economic sector to the government system. While it brings significant benefits, AI also poses legal and ethical risks that have not been fully addressed in the current international legal framework. This research aims to analyze the regulation of the use of AI from the perspective of international law and identify challenges and opportunities in shaping a global legal framework that is responsive to the development of AI. This study uses a normative juridical method with a conceptual approach and legal comparison. The legal materials used include international legal instruments such as the Universal Declaration of Human Rights (UDHR), the International Covenant on Civil and Political Rights (ICCPR), soft law documents such as the UNESCO Recommendation on the Ethics of Artificial Intelligence, and regional regulations such as the EU Artificial Intelligence Act. The results show that there is no specific binding international agreement related to AI, so there is a legal vacuum in the regulation. This disintegration of international legal norms has implications for weak human rights protection mechanisms, unclear legal responsibility for the impact of AI, and weak governance of technology across countries. In addition, regulations that are unilateral or regional, such as those carried out by the European Union, have the potential to create a regulatory gap between developed and developing countries. This study concludes that it is necessary to establish a binding, inclusive, and ethical international legal framework for regulating the use of AI.